Media Pembelajaran Anak Usia Dini Dengan Animasi Interaktif Berbasis ActionScript - Supriyadi Sandi (Universitas Bina Sarana Informatika, 2020)
Abstract – Early childhood education is a level of basic education which is an educational effort aimed at children aged two years to six years, which is carried out through the provision of education to help growth, physical and spiritual development so that children have readiness to enter further education. Education is provided on the track formal, nonformal and informal. This research will make actionscript based education applications. In making this application, observation or direct observation is needed to find out how far the children receive the material given by the teacher in the classroomand what obstacles affect children's concentration in the problem. So that the application can match what is needed. Adobe Flash player is software that functions to run various kinds of multimedia files created in the Adobe Flash platform. This application was originally available for a variety of computer or mobile operating systems, including Adobe Flash Player for Android.Results of research produces educational applications,as a means to support the children's interest in learning outside of school, at home. So that children do not miss the material given by the teacher in the classroom. And material can be quickly accepted by children. Keywords : Learning Media, Letters and Numbers, Actionscrip